Technical Guidance for Making Date Milk Product Labels - Vernanda, Genesa; Istia, Maria Nino; Katuruni, Innas Rovino; Ariyanti, Tika Dwi; Praptiwi, Rahma Nur; Lukitaningrum, Kristin; Rahmawati, Anita; Untari, Sri Isti (Journal of Innovative and Creativity, 2026)
Through community service activities, the implementing team will provide education to MSME groups that produce date milk. This activity includes counseling on creating attractive and informative product labels. The main objective of this activity is to increase the capacity of MSMEs to manage their businesses professionally, legally, and with high competitiveness in an increasingly competitive market. The implementation of this community service activity includes education on the importance of product labels and label-making procedures. This series of activities will be carried out from June to October 2025. The result of this community service activity is the availability of new product logos and labels tailored to marketing strategies.